SIBS graft copolymer, preparation method thereof and intraocular lens

By grafting vinyl compounds of functional groups on SIBS to form SIBS graft copolymers, the problems of biomolecular adhesion and inflammatory response in biomedical applications are solved, and the hydrophilicity and biocompatibility are improved Sexual effect.

CN119161587APending Publication Date: 2024-12-20CHENGDU MIGOS MEDICAL TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310725172.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-06-19
Publication Date
2024-12-20

AI Technical Summary

Technical Problem

In biomedical applications, SIBS materials are caused by poor surface inertia and hydrophilicity, which leads to biomolecules, affects biocompatibility and increases the risk of inflammatory response.

Method used

By grafting vinyl compounds with functional groups on SIBS, SIBS graft copolymers are formed, which improves their hydrophilicity and reduces the water contact angle, reduces the adhesion of proteins, cells and bacteria, and improves biocompatibility.

Benefits of technology

It significantly reduces the water contact angle of SIBS graft copolymer, reduces inflammatory response, improves biocompatibility and optical properties, and enhances its application prospects in the field of biomedical science.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119161587A_ABST
    Figure CN119161587A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of biomedical materials, in particular to an SIBS graft copolymer, a preparation method thereof and an artificial lens. The SIBS grafted copolymer comprises SIBS and a biological material grafted to the SIBS, and the biological material is grafted to the SIBS through a vinyl compound with a functional group. The water contact angle of the SIBS grafted copolymer is obviously reduced relative to that of SIBS, which indicates that the SIBS grafted copolymer has good hydrophilicity, is not easy to adhere protein, cells, bacteria and the like, and can reduce the formation of inflammation. And meanwhile, the optical property and the biocompatibility are relatively good.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of biomedical materials, and in particular to a SIBS graft copolymer and a preparation method thereof and an artificial lens. Background Art

[0002] SIBS stands for poly(styrene-b-isobutylene-b-styrene) triblock copolymer, a thermoplastic elastomer synthesized by active cationic polymerization and a transparent material. In clinical trials of ophthalmic implantation, it was found that no obvious scars or wrapping would appear around the implant. Since the polyisobutylene chain has a saturated, non-polar structure and does not contain groups that are susceptible to chemical or oxidative attacks, it can be used as a long-term implantable material without degradation. However, due to the poor inertness and hydrophilicity of the SIBS material surface, it is easy to produce non-specific effects in the environment where it encounters biological molecules, causing a large number of biological molecules to attach, affecting its application prospects in the biomedical field.

[0003] In particular, when the biomaterials prepared by SIBS come into contact with body fluids, the surface will be adsorbed by plasma proteins, and this initial adsorbed protein layer will affect the formation of thrombi and cell reactions. At the same time, in this process, the surface of the biomaterial is a key area for interaction with the in vivo environment. These interactions may lead to poor biocompatibility of the biomaterial surface and increase the risk of adverse reactions such as inflammatory reactions.

[0004] Therefore, SIBS needs to be modified to improve its hydrophilicity and further enhance its biocompatibility.

[0005] In view of this, the present invention is proposed. Summary of the invention

[0006] The purpose of the present invention is to provide a SIBS graft copolymer and a preparation method thereof and an artificial lens. The SIBS graft copolymer provided in the embodiment of the present invention has a significantly lower water contact angle than SIBS, indicating that it has good hydrophilicity, is not easy to adhere to proteins, cells and bacteria, etc., and can reduce the formation of inflammation. At the same time, it has good optical properties and biocompatibility.

[0007] The present invention is achieved in that:

[0008] In a first aspect, the present invention provides a SIBS graft copolymer, which comprises a SIBS and a biomaterial grafted to the SIBS, wherein the biomaterial is grafted to the SIBS via a vinyl compound having a functional group.

[0009] In an optional embodiment, the number average molecular weight of the biomaterial is 700 to 100,000, preferably 1,000 to 10,000;

[0010] The biomaterial is selected from one or two of hyaluronic acid, collagen, gelatin, alginate or chitosan, starch, cellulose and polyethylene glycol, preferably hyaluronic acid or collagen.

[0011] In an optional embodiment, the vinyl compound having a functional group is selected from one of glycidyl methacrylate, acrylic acid, methacrylic acid, acrylamide and hydroxyethyl methacrylate.

[0012] In an optional embodiment, the number average molecular weight of the SIBS is 20,000 to 100,000, preferably 30,000 to 60,000.

[0013] In an optional embodiment, the grafting rate of the biomaterial onto the SIBS is 0.5-30%, preferably 0.5-10%.

[0014] In an optional embodiment, the water contact angle of the SIBS graft copolymer is 0-90 degrees, preferably 10-65 degrees.

[0015] In a second aspect, the present invention provides a method for preparing the SIBS graft copolymer described in the aforementioned embodiment, comprising: grafting a biomaterial onto SIBS using a vinyl compound having a functional group.

[0016] In an alternative embodiment, the grafting method comprises a surface graft copolymerization method.

[0017] In an optional embodiment, the preparation method of the SIBS graft copolymer is selected from any one of the following methods:

[0018] (1) SIBS is grafted and copolymerized with vinyl compounds having functional groups, and then the functional groups on the vinyl graft chains react with biomaterials to form SIBS graft copolymers;

[0019] (2) reacting a vinyl compound having a functional group with a biomaterial to form a biofunctionalized vinyl compound, which is then graft-copolymerized with SIBS to form a SIBS graft copolymer.

[0020] In a third aspect, the present invention provides an artificial lens prepared using the SIBS graft copolymer described in the aforementioned embodiment.

[0021] The present invention has the following beneficial effects: the embodiment of the present invention grafts biomaterials onto SIBS through vinyl compounds having functional groups, which can significantly reduce the water contact angle of SIBS, improve its hydrophilicity, reduce the adhesion of proteins, cells and bacteria on the SIBS graft copolymer, and reduce the inflammatory response caused by the artificial lens formed by using the SIBS graft copolymer. At the same time, the biocompatibility of the SIBS graft copolymer can be improved. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.

[0023] Figure 1 The SEM image of the SIBS graft copolymer provided in the embodiment of the present invention;

[0024] Figure 2 The UV-visible spectrum of the SIBS graft copolymer provided in the embodiment of the present invention;

[0025] Figure 3 The cytotoxicity test results of the SIBS graft copolymer provided in the embodiments of the present invention. DETAILED DESCRIPTION

[0026] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.

[0027] An embodiment of the present invention provides a SIBS graft copolymer, which includes a SIBS and a biomaterial grafted to the SIBS, wherein the biomaterial is grafted to the SIBS via a vinyl compound having a functional group.

[0028] In the embodiment of the present invention, SIBS is used as the main chain, and the biofunctional material is a branched biofunctionalized SIBS, so as to improve its hydrophilicity, biocompatibility and optical properties.

[0029] The number average molecular weight of the biomaterial is 700 to 100,000, preferably 1,000 to 10,000, for example, 700, 1,000, 5,000, 8,000, 10,000, 50,000, 1,000,000, or any other number between 700 and 100,000.

[0030] The biomaterial is selected from one or two of hyaluronic acid, collagen, gelatin, alginate or chitosan, starch, cellulose and polyethylene glycol, preferably hyaluronic acid or collagen.

[0031] The vinyl compound having a functional group is selected from one of glycidyl methacrylate, acrylic acid, methacrylic acid, acrylamide and hydroxyethyl methacrylate.

[0032] The number average molecular weight of SIBS is 20,000 to 100,000, preferably 30,000 to 60,000.

[0033] Furthermore, the grafting rate of the biomaterial grafted onto the SIBS is 0.5-30%, preferably 0.5-10%. The water contact angle of the SIBS graft copolymer is 0-90 degrees, preferably 10-65 degrees.

[0034] In a second aspect, the present invention provides a method for preparing the SIBS graft copolymer described in the aforementioned embodiment, comprising: grafting a biomaterial onto SIBS using a vinyl compound having a functional group.

[0035] The grafting method used includes surface grafting copolymerization method.

[0036] The embodiments of the present invention are described as follows:

[0037] (1) reacting a vinyl compound having a functional group with a biomaterial to form a biofunctionalized vinyl compound, and then graft-copolymerizing the vinyl compound with SIBS to form a SIBS graft copolymer. Specifically:

[0038] (a) Preparation of biomaterials capable of free radical polymerization

[0039] The biomaterial is dissolved in a polar solvent, and then a vinyl compound with a functional group is added, and the reaction is carried out at 0-70°C for a certain period of time. After the reaction is completed, a precipitant is added to precipitate the product, and the product is separated and washed and then freeze-dried to form a biomaterial that can undergo free radical polymerization.

[0040] The polar solvent described in the above preparation method is one of water, N,N'-dimethylformamide, N,N'-dimethylacetamide, N,N'-dimethylpropionamide, N,N'-dimethylacetamide, N,N'-diethylacetamide, N,N'-diethylpropionamide, dimethyl sulfoxide, diethyl sulfoxide, ether, tetrahydrofuran, dioxane, acetone, butanone, cyclohexanone or a mixture thereof, preferably water, N,N'-dimethylformamide, dimethyl sulfoxide, acetone, ether, tetrahydrofuran; the precipitant is one of methanol, ethanol, isopropanol, butanol, octanol, ethylene glycol, glycerol, preferably methanol, ethanol, isopropanol.

[0041] The reaction temperature in the above preparation method is 0-70°C, preferably 20-60°C; the reaction time is 6h-7 days, preferably 12h-6 days.

[0042] (b) preparing SIBS graft copolymers;

[0043] The SIBS film was immersed in the photoinitiator solution for 10 minutes and air-dried at room temperature. The air-dried SIBS was immersed in the biomaterial solution prepared in (a) that can undergo free radical polymerization, and the SIBS graft copolymer sample was obtained under ultraviolet light irradiation. The sample was taken out, rinsed three times with deionized water, and air-dried at room temperature.

[0044] The photoinitiator described in the above preparation method is one or more of benzophenone, 2,4-dihydroxybenzophenone, diphenylacetophenone, 2,2-dimethoxy-2-phenylacetophenone, and 2-methyl-1-(4-methylthiophenyl)-2-morpholine-1-propanone.

[0045] In the above step (b), the ultraviolet light intensity is 400W to 1000W, the illumination time is 1min to 30min, preferably 4min to 15min, and the polymerization temperature is 0 to 50°C, preferably 20°C to 30°C.

[0046] In the above step (b), the solvent used to dissolve the photoinitiator is one or two of methanol, ethanol, methanol, ethanol, isopropanol, butanol, octanol, ethylene glycol, and glycerol, preferably ethanol and methanol.

[0047] (2) SIBS is grafted and copolymerized with vinyl compounds having functional groups, and then the functional groups on the vinyl grafted chains react with biomaterials to form SIBS grafted copolymers. The details are as follows:

[0048] (a) Preparation of SIBS graft copolymers with vinyl side chains

[0049] The SIBS film is immersed in a photoinitiator solution for a certain period of time and air-dried at room temperature. The air-dried SIBS is immersed in a solution of a vinyl compound having a functional group and irradiated with ultraviolet light to obtain a SIBS graft copolymer with a vinyl side chain. The sample is taken out, rinsed three times with deionized water, and air-dried at room temperature.

[0050] The photoinitiator described in the above preparation method is one or more of benzophenone, 2,4-dihydroxybenzophenone, diphenylacetophenone, 2,2-dimethoxy-2-phenylacetophenone, and 2-methyl-1-(4-methylthiophenyl)-2-morpholine-1-propanone.

[0051] In the above step (a), the ultraviolet light intensity is 400W to 1000W, the illumination time is 1min to 30min, preferably 4min to 15min, and the polymerization temperature is 0 to 50°C, preferably 20°C to 30°C.

[0052] In the above step (a), the solvent used to dissolve the photoinitiator is one or two of methanol, ethanol, methanol, ethanol, isopropanol, butanol, octanol, ethylene glycol, and glycerol, preferably ethanol and methanol.

[0053] (b) Preparation of SIBS graft copolymers

[0054] The SIBS graft copolymer with vinyl side chains was placed in a PBS solution and activated by adding an EDC solution. Then, a mixed EDC / NHS and biomaterial were added and reacted at 0-70°C for a certain time to prepare a biofunctionalized SIBS. Finally, the sample was rinsed three times with deionized water and freeze-dried in a freeze drying oven.

[0055] The reaction temperature in the above preparation method is 0-70°C, preferably 20-60°C; the reaction time is 6h-7 days, preferably 12h-6 days.

[0056] The calculation of the grafting rate provided in the embodiment of the present invention is as follows:

[0057] Grafting rate (G%):

[0058] G%=(m1-m0) / m0

[0059] Where: G%-surface grafting rate; m0-film mass before grafting; m1-film mass after grafting.

[0060] Water contact angle measurement: 50 μL of water was dropped on the material surface, and the state of the water drop was recorded using a water contact angle measuring device. Finally, the water contact angle in the recorded video was calculated using custom software.

[0061] Scanning electron microscopy (SEM) determination: SEM was used to observe the surface morphology of the material.

[0062] Transmittance measurement: The transmittance of the film was measured using a UV-2450 ultraviolet-visible spectrophotometer from Shimadzu Corporation of Japan, with a wavelength range of 300-1100 nm.

[0063] MTT assay to evaluate in vitro cytotoxicity: cells were plated at 1×10 4Inoculate each well with 100 μL / well of 4 concentrations of extracts prepared with the culture medium, culture for 24 hours, discard the original culture medium, add 100 μL / well of 4 concentrations of extracts prepared with the culture medium, incubate for 24 hours, remove the extracts, and add MTT solution to each well. After the culture plate is cultured for another 3 hours, remove the MTT solution and add 100 μL / well of isopropanol. Use a microplate reader to measure the absorbance of the culture plate at 570 nm as the measurement wavelength and 650 nm as the reference wavelength.

[0064] The features and performance of the present invention are further described in detail below in conjunction with the embodiments.

[0065] Example 1

[0066] The embodiment of the present invention provides a method for preparing a SIBS graft copolymer, comprising:

[0067] 1.0 g of HA was dissolved in PBS with a pH of 3.0 and adjusted with aqueous hydrochloric acid to prepare a 10% (w / v) solution. Then 2.2 mL of GMA was added and stirred vigorously at room temperature for 6 days. After the reaction was completed, the solution was precipitated with excess methanol to remove unreacted impurities, and then dried in a freeze dryer to obtain the GMHA product.

[0068] The SIBS film was immersed in a BP solution (concentration of 10%) for 10 minutes and air-dried at room temperature. The air-dried SIBS was immersed in a GMHA solution and irradiated with ultraviolet light to obtain a cross-linked SIBS-GMHA sample. The sample was taken out, rinsed with deionized water three times, air-dried at room temperature, and weighed.

[0069] Example 2-Example 11

[0070] The SIBS graft copolymer was prepared by referring to the preparation method provided in Example 1, except that the amount of SIBS and GMHA used and the exposure time were different, as shown in Table 1. At the same time, the grafting rate and water contact angle of the SIBS graft copolymers of Examples 1-11 were tested, and the results are shown in Table 1. The water contact angle of SIBS was measured to be 105 degrees.

[0071] Table 1

[0072]

[0073]

[0074] According to Table 1, in Examples 1-5, as the illumination time increases, the grafting rate and the water contact angle show a trend of first increasing and then decreasing. This is because the free radical polymerization generated by light initiation allows the double bonds in GMHA to be opened and connected to the surface of SIBS. However, if the illumination time is too long, the heat generated by the ultraviolet lamp is too large, which will cause the surface of the film to age rapidly, thereby affecting the grafting efficiency. Through Examples 1-5, it can be determined that when the illumination time is 6 minutes, the best grafting effect is 3.82%, and the best hydrophilic property is 48°.

[0075] It can be seen from Examples 6-11 that when the GMHA monomer concentration is too high, the probability of self-polymerization will increase, thereby reducing the number of monomers involved in the copolymerization reaction, affecting the progress of the grafting copolymerization reaction, and then resulting in a decrease in the grafting rate. In addition, the thickness of the GMHA grafted layer will also increase, and may eventually reach a saturated state. Continuing to increase the GMHA concentration will hinder the grafting of new monomers, resulting in a decrease in the grafting rate. In summary, when the GMHA solution concentration is 17g, the grafting rate reaches a maximum value of 2.61%. It can be seen from the contact angle that after grafting hyaluronic acid, the contact angle becomes less than 90°. When the GMHA concentration is low, the grafted GMHA content is relatively small, and the coverage area of ​​the grafted carboxyl functional group is relatively small, so the hydrophilicity does not change much. When the GMHA concentration continues to increase, the coverage area of ​​the grafted carboxyl functional group increases, making the SIBS surface more hydrophilic, so the hydrophilic property is improved. However, when the GMHA concentration is too high, the grafting density is too large, which may cause cross-linking and aggregation, resulting in a decrease in hydrophilicity. Therefore, the change of grafting density is the main reason affecting the change of hydrophilic properties.

[0076] Example 12

[0077] The embodiment of the present invention provides a method for preparing a SIBS graft copolymer, comprising:

[0078] The SIBS film was immersed in the BP solution for 10 minutes and air-dried at room temperature. The air-dried SIBS was immersed in the GMA solution and irradiated with ultraviolet light to obtain a cross-linked SIBS-GMA sample.

[0079] The sample was removed, rinsed three times with deionized water, air-dried at room temperature, and weighed. The SIBS-GMA membrane was immersed in a 50 mM EDC solution and activated at 37 °C for 1 hour. Then, mixed EDC / NHS and hyaluronic acid were added and reacted at 37 °C for 24 hours to prepare SIBS-GMA-HA. Finally, the sample was rinsed three times with deionized water, placed between two slides, and freeze-dried in a freeze drying oven.

[0080] Example 13-Example 26

[0081] The SIBS graft copolymer was prepared by referring to the preparation method provided in Example 12, except that the SIBS and GMA dosages and the exposure time were different, as shown in Table 2 and Table 3. At the same time, the grafting rate and water contact angle of the SIBS graft copolymers of Examples 12-26 were tested, and the results are shown in Table 2 and Table 3. The water contact angle of SIBS was measured to be 105 degrees.

[0082] Table 2

[0083]

[0084] Note: The grafting rate in Table 2 refers to the grafting rate of GMA

[0085] Table 3

[0086]

[0087]

[0088] Note: The grafting rate in Table 3 refers to the grafting rate of HA

[0089] As shown in Table 2, in Examples 12-16, the effect of the photoinitiator BP concentration on the GMA grafting rate was investigated. According to the grafting results, it can be concluded that a too high photoinitiator BP concentration will lead to a lower grafting rate, because a too high benzophenone concentration will have a shielding effect, causing the reaction solution to absorb more ultraviolet light, reducing the ultraviolet light absorption intensity on the surface of the SIBS film, and reducing the GMA grafting rate. At the same time, an increase in the number of free radicals will also increase the termination reaction of the long chain. In summary, according to the infrared spectrum and the results of the grafting rate, when n BP :n GMA When the ratio is 5:100, the grafting reaction efficiency is the best, and the grafting rate reaches a maximum of 2.68%.

[0090] In Examples 17-21, based on the results obtained in Cases 12-16, it is determined that n BP :n GMA =5:100, the grafting reaction efficiency is optimal. Keeping this reaction condition, continue to explore the effect of UV irradiation time on the grafting rate of glycidyl methacrylate. From the results of the grafting rate, it can be seen that the grafting rate first increases and then decreases with the increase of UV irradiation time. When the irradiation time is 5min, the grafting rate is as high as 3.37%. This is because ultraviolet light can excite the photoinitiator to produce free radicals, which in turn initiates the free radical polymerization reaction of the GMA monomer and increases the grafting rate. However, too long an irradiation time will cause chain transfer to occur, making it difficult for macromolecular chains to form. At the same time, an increase in the grafting rate will also increase steric hindrance, hindering the further grafting of GMA, resulting in a decrease in the grafting rate. Therefore, when the irradiation time is 5min, the grafting reaction effect is best. In Examples 22-26, it can be determined based on the above experimental results that nBP :n GMA =5:100, when the illumination time is 5min, the grafting reaction efficiency is the best. Keeping this reaction condition, continue to explore the effect of GMA solution concentration on the grafting reaction rate. From the results of the grafting rate, it can be seen that the grafting rate shows a trend of first increasing and then decreasing with the increase of GMA solution concentration. This is because during the grafting reaction, GMA molecules react with free radicals on the surface of the film to form grafted copolymers. The higher the GMA concentration, the more GMA monomers participate in the grafting copolymerization reaction, thereby increasing the grafting reaction of GMA molecules. Therefore, the grafting rate will increase with the increase of GMA concentration. However, when the GMA concentration continues to increase, the probability of GMA self-polymerization increases, resulting in a downward trend in the grafting rate. In summary, when the GMA solution concentration is 25%, the grafting reaction efficiency is the best, and the grafting rate reaches a maximum value of 2.31%.

[0091] As can be seen from Table 3, in Examples 22-26, the prepared SIBS-GMA with different GMA solution concentrations was grafted and copolymerized with a fixed mass of HA (0.5 g) to explore the effect of GMA solution concentration on the grafting rate of SIBS-GMA-HA. From the results of the grafting rate, it can be seen that with the increase in the concentration of the GMA solution, the grafting rate shows a trend of first increasing and then decreasing. This is because with the increase in the concentration of the GMA solution, the amount of GMA grafted to the surface of SIBS increases, which in turn leads to an increase in the number of HA reacting with GMA, so the grafting rate of HA increases; however, when the amount of GMA is too much, the probability of GMA self-polymerization increases, which in turn affects the number of GMA grafted to the surface of SIBS, which in turn leads to a decrease in the number of HA reacting with GMA, resulting in a decrease in the grafting rate of HA. The results of the water contact angle measurement show that after hyaluronic acid is grafted on the surface of SIBS, the hydrophilicity of the material surface can be significantly improved, and the surface of the material is transformed from a hydrophobic material to a hydrophilic material. When the GMA concentration increased from 15% to 20%, the contact angle gradually decreased; and when the GMA concentration increased to 25%, the contact angle dropped rapidly to 64°. With the further increase of GMA concentration, the change of contact angle was no longer obvious. In summary, when nBP:nGMA=5:100 and the concentration of GMA solution was 25%, the HA grafting rate reached a maximum value of 1.73%, and the water contact angle was 64°.

[0092] In Examples 27-31, according to the above conditions, it can be determined that when the ultraviolet irradiation time is 5 min, the molar ratio of the photoinitiator BP to the grafting monomer GMA is nBP:nGMA=5:100, and the concentration of the GMA solution is 25%, the grafting efficiency is optimal. Maintaining the reaction conditions, changing the mass of HA (0.5g, 0.7g, 0.9g, 1.1g, 1.3g), explore the effect of HA dosage on the SIBS-GMA-HA coupling reaction. From the results of the grafting rate, it can be seen that the grafting rate shows a trend of first increasing and then decreasing. This is because as the mass of HA feed increases, the probability of HA reacting with GMA increases, which increases the steric hindrance of HA molecules during the grafting process, making it difficult to further graft to the SIBS surface. Therefore, the grafting rate will show a trend of first increasing and then decreasing. The water contact angle test results show that as the amount of HA increases, the hydrophilicity changes significantly, the material surface changes from hydrophobic material to hydrophilic material, and the hydrophilicity gradually improves. However, as the concentration of hyaluronic acid continues to increase, the hydrophilicity begins to decrease. This is because when the concentration of HA is too high, the probability of hydrogen bonds between hyaluronic acid molecules increases, and the probability of SIBS-GMA-HA combining with water molecules decreases, resulting in a decrease in the hydrophilicity of the SIBS-GMA-HA surface. In summary, the concentration needs to be controlled when grafting HA. When the feed is 1.1g, the best hydrophilicity is 64°.

[0093] Test Example 1

[0094] The SIBS raw material; SIBS-GMA formed in Example 20; SIBS-GMHA formed in Example 7 and SIBS-GMA-HA in Example 24 were respectively subjected to SEM detection. The detection results are shown in Figure 1 .

[0095] Figure 1 In the table, a represents SIBS, b represents SIBS-GMA, c represents SIBS-GMHA, and d represents SIBS-GMA-HA. According to Table 1, the desired SIBS graft copolymer is successfully prepared in the embodiment of the present invention.

[0096] Test Example 2

[0097] The SIBS raw material, the SIBS-GMHA formed in Example 7, and the SIBS-GMA-HA formed in Example 30 were subjected to UV detection, respectively. Figure 2 .

[0098] according to Figure 2It can be seen that the transmittance of the unmodified SIBS film to visible light is only about 71%, while the transmittance of the SIBS film modified with hyaluronic acid is improved. The light transmittance of the hyaluronic acid-modified SIBS films SIBS-GMHA and SIBS-GMA-HA prepared by the two methods is not much different, and the maximum transmittance can reach 80%.

[0099] Test Example 3

[0100] The in vitro cytotoxicity of SIBS-GMHA formed in Example 3 was evaluated using MTT assay.

[0101] Table 4 Effects of membrane material extracts on L929 cell activity

[0102]

[0103]

[0104] Note: * p<0.05, ** p<0.01, ** p<0.001 compared with the control group.

[0105] according to Figure 3 As shown in the results of Table 4, after the L929 cells were treated with the extracts for 24 h, there was no significant change in the cell morphology of each extract group compared with the control group, and there was no significant difference in cell activity (p>0.05).

[0106] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A SIBS graft copolymer, characterized in that: The invention comprises a SIBS and a biomaterial grafted to the SIBS, wherein the biomaterial is grafted to the SIBS via a vinyl compound having a functional group.

2. The SIBS graft copolymer according to claim 1, characterized in that The number average molecular weight of the biomaterial is 700 to 100,000, preferably 1,000 to 10,000; The biomaterial is selected from one or two of hyaluronic acid, collagen, gelatin, alginate or chitosan, starch, cellulose and polyethylene glycol, preferably hyaluronic acid or collagen.

3. The SIBS graft copolymer according to claim 1, characterized in that The vinyl compound having a functional group is selected from one of glycidyl methacrylate, acrylic acid, methacrylic acid, acrylamide and hydroxyethyl methacrylate.

4. The SIBS graft copolymer according to claim 1, characterized in that The number average molecular weight of the SIBS is 20,000 to 100,000, preferably 30,000 to 60,000.

5. The SIBS graft copolymer according to claim 1, characterized in that The grafting rate of the biomaterial onto the SIBS is 0.5-30%, preferably 0.5-10%.

6. The SIBS graft copolymer according to claim 1, characterized in that The water contact angle of the SIBS graft copolymer is 0-90 degrees, preferably 10-65 degrees.

7. A method for preparing the SIBS graft copolymer according to claim 1, characterized in that: include: Vinyl compounds with functional groups are used to graft biomaterials onto SIBS.

8. The preparation method according to claim 7, characterized in that: The grafting method includes a surface graft copolymerization method.

9. The preparation method according to claim 7, characterized in that: The preparation method of the SIBS graft copolymer is selected from any one of the following methods: (1) SIBS is grafted and copolymerized with vinyl compounds having functional groups, and then the functional groups on the vinyl graft chains react with biomaterials to form SIBS graft copolymers; (2) reacting a vinyl compound having a functional group with a biomaterial to form a biofunctionalized vinyl compound, which is then graft-copolymerized with SIBS to form a SIBS graft copolymer.

10. An artificial lens, characterized in that: It is prepared using the SIBS graft copolymer described in claim 1.